2020
DOI: 10.26879/1062
|View full text |Cite
|
Sign up to set email alerts
|

Geometric morphometric assessment of Guanshan trilobites (Yunnan Province, China) reveals a limited diversity of palaeolenid taxa

Abstract: The Guanshan Biota is a typical Burgess Shale-type Cambrian-aged Lagerstätte with diverse trilobites. As such, the taxonomy of trilobites from the Guanshan Biota, especially the palaeolenid group, has been the focus of research over the last decade. To develop this research, we present a geometric morphometric analysis of cranidial shape in 60 specimens from three sections of the Guanshan Biota from the Wulongqing Formation (Cambrian Series 2, Stage 4), Yunnan Province, South China. We show that cranidia of Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…This study reported on Tuzoia from the Guanshan Biota (Wulongqing Formation, Cambrian Series 2, Stage 4), a representative Burgess Shale-type biota from southwestern China that included several categories of soft-bodied metazoans (Luo et al, 2005;Li et al, 2006;Luo et al, 2006;Hu et al, 2007;Luo et al, 2007;Yang et al, 2008.;Hu et al, 2010a;Hu et al, 2010b;Liu et al, 2012;Hu et al, 2013;Liu et al, 2015;Liu et al, 2016;Li et al, 2017;Yang et al, 2018;Wu and Liu. 2019;Chen et al, 2020;Zhao et al, 2020). More than 60 taxa have been described from this biota, belonging to more than ten animal groups and algae, including arthropods, brachiopods, vetulicolians, lobopodians, sponges, eocrinoid echinoderms, hyolithids, polychaetes, priapulids, chancelloriids, eldonoids, and problematic fossils (Luo et al, 2005;Li et al, 2006;Luo et al, 2006;Hu et al, 2007;Luo et al, 2007;Yang et al, 2008.;Hu et al, 2010a;Hu et al, 2010b;Liu et al, 2012;Hu et al, 2013;Liu et al, 2015;Liu et al, 2016;Li et al, 2017;Yang et al, 2018;Zhao et al, 2018;Wu and Liu.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study reported on Tuzoia from the Guanshan Biota (Wulongqing Formation, Cambrian Series 2, Stage 4), a representative Burgess Shale-type biota from southwestern China that included several categories of soft-bodied metazoans (Luo et al, 2005;Li et al, 2006;Luo et al, 2006;Hu et al, 2007;Luo et al, 2007;Yang et al, 2008.;Hu et al, 2010a;Hu et al, 2010b;Liu et al, 2012;Hu et al, 2013;Liu et al, 2015;Liu et al, 2016;Li et al, 2017;Yang et al, 2018;Wu and Liu. 2019;Chen et al, 2020;Zhao et al, 2020). More than 60 taxa have been described from this biota, belonging to more than ten animal groups and algae, including arthropods, brachiopods, vetulicolians, lobopodians, sponges, eocrinoid echinoderms, hyolithids, polychaetes, priapulids, chancelloriids, eldonoids, and problematic fossils (Luo et al, 2005;Li et al, 2006;Luo et al, 2006;Hu et al, 2007;Luo et al, 2007;Yang et al, 2008.;Hu et al, 2010a;Hu et al, 2010b;Liu et al, 2012;Hu et al, 2013;Liu et al, 2015;Liu et al, 2016;Li et al, 2017;Yang et al, 2018;Zhao et al, 2018;Wu and Liu.…”
Section: Introductionmentioning
confidence: 99%
“…More than 60 taxa have been described from this biota, belonging to more than ten animal groups and algae, including arthropods, brachiopods, vetulicolians, lobopodians, sponges, eocrinoid echinoderms, hyolithids, polychaetes, priapulids, chancelloriids, eldonoids, and problematic fossils (Luo et al, 2005;Li et al, 2006;Luo et al, 2006;Hu et al, 2007;Luo et al, 2007;Yang et al, 2008.;Hu et al, 2010a;Hu et al, 2010b;Liu et al, 2012;Hu et al, 2013;Liu et al, 2015;Liu et al, 2016;Li et al, 2017;Yang et al, 2018;Zhao et al, 2018;Wu and Liu. 2019;Chen et al, 2020;Zhao et al, 2020). Among the large bivalved arthropods from the Wulongqing Formation, Tuzoia ranked second, after Isoxys.…”
Section: Introductionmentioning
confidence: 99%
“…The metrics currently in use in fire science, such as burn area, fire perimeter, and fire‐line depth, do not sufficiently capture the detailed nature of the dynamic development of burned area morphologies. Different morphometry approaches exist in other disciplines, including botany (Belcher, 2016; Chuanromanee et al., 2019; Klein & Svoboda, 2017; Viscosi & Cardini, 2011), geomorphology (Cannon & Gartner, 2007; Whitten & Martin, 2019; Zhao et al., 2020), and medical research (Chollet et al., 2014; Claes et al., 2012; Mitteroecker et al., 2013). These approaches were designed for different physical systems and are not directly applicable to capturing details specific to fire behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been used on trilobites (e.g. Hopkins & Webster 2009;Webster 2011;Abe & Lieberman 2012;Gendry et al 2013;Esteve et al 2017;Álvaro et al 2018;Bicknell et al 2019;Oudot et al 2019;Álvaro & Esteve 2020;Zhao et al 2020). In this study, we used landmarks on the trilobite's cephalon for geometric morphological analysis.…”
Section: Geometric Morphometric Methodsmentioning
confidence: 99%